Tantalum-containing mesoporous bioactive glass powder for hemostasis. (March 2021) - Nagrath, Malvika; Gallant, Reid; Yazdi, Alireza Rahimnejad; Mendonca, Andrew; Rahman, Saidur; Chiu, Loraine; Waldman, Stephen D; Ni, Heyu; Towler, Mark R
This study evaluates the hemostatic properties of tantalum-containing mesoporous bioactive glasses (Ta-MBGs) through a suite of in-vitro methods: hemolysis percentage, zeta potential, blood coagulation assays (Activated Partial Thromboplastin Time – APTT and Prothrombin Time - PT) and cytotoxicity tests. Five compositions of Ta-MBG, with x mol% Ta2 O5 added to the glass series (80- x )SiO2 -15CaO-5P2 O5 - x Ta2 O5 where x =0 (0Ta), x =0.5 (0.5Ta), x =1 (1Ta), x =5 (5Ta), and x =10 (10Ta) mol%, were synthesised. The hemostatic potential of all the Ta-MBGs was confirmed by their negative zeta potential (–23 to –31 mV), which enhances the intrinsic pathway of blood coagulation. The hemolysis percentages of all Ta-MBGs except 10Ta showed statistically significant reductions compared to the same experiments carried out both in the absence of a sample ('no treatment' group) and in the presence of 10Ta. These observations validate the consideration of Ta-MBGs as hemostatic agents as they do not cause significant lysis of red blood cells. Cytotoxicity analysis revealed that Ta-MBGs had no effect on bovine fibroblast viability. Furthermore, a reduction in both APTT (a test to evaluate the intrinsic pathway of coagulation) and PT (a test to evaluate the extrinsic pathway) signified enhancement of hemostasis: 5Ta caused a significant reduction in APTT compared to 'no treatment', 1Ta and 10Ta and a significant reduction in PT compared to 0Ta. Therefore, we conclude that 5mol% of Ta optimised the hemostatic properties of these mesoporous bioactive glasses.